Build a bag book Backpacks : sew 15 stunning projects and endless variations - Shore, Debbie (Tunbridge Wells, Kent Search Press, 2020)
Create 15 stunning backpacks using Debbie's easy-to-follow instructions and the reusable plastic template
1
Keywords: Backpacks -- Design; Bags; Sewing